2010
DOI: 10.4061/2010/854526
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Endoglucanase Production byTrichoderma harzianumIOC-3844 Cultivated in Pretreated Sugarcane Mill Byproduct

Abstract: The low-cost production of cellulolytic complexes presenting high action at mild conditions and well-balanced cellulase activities is one of the major bottlenecks for the economical viability of the production of cellulosic ethanol. In the present paper, the filamentous fungus Trichoderma harzianum IOC-3844 was used for the production of cellulases from a pretreated sugarcane bagasse (namely, cellulignin), by submerged fermentation. This fungal strain produced high contents of endoglucanase activity (6,358 U·L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 43 publications
2
38
2
2
Order By: Relevance
“…The K m is similar to that found for endoglucanase activity in the crude extract of T. harzianum IOC-3844 (19 g/L) and the endoglucanase from T. harzianum ETS 323 (23 g/L) (de Castro et al, 2010a;Liu et al, 2010). This lower specificity in comparison to T. reesei does not preclude the use of this enzyme in saccharification, since a high cellulose concentration is used in this process.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The K m is similar to that found for endoglucanase activity in the crude extract of T. harzianum IOC-3844 (19 g/L) and the endoglucanase from T. harzianum ETS 323 (23 g/L) (de Castro et al, 2010a;Liu et al, 2010). This lower specificity in comparison to T. reesei does not preclude the use of this enzyme in saccharification, since a high cellulose concentration is used in this process.…”
Section: Discussionsupporting
confidence: 55%
“…However, at about 48°C (the optimal temperature of rThEGIII), high endoglucanase activity was also detected in the fungal extract (de Castro et al, 2010a). This difference between the crude extract and the purified rThEGIII could be explained by the existence of other endoglucanases and the synergy among them within the fungal culture supernatant.…”
Section: Discussionmentioning
confidence: 98%
“…T. harzianum are frequently reported as control agent against fungal pathogens (Arantes and Saddler 2010;Banerjee et al 2010). However, recent studies have also revealed the potential of this fungus for cellulase production and industrial applications (Ahmed et al 2009;Castro et al 2010aCastro et al , 2010b. Likewise, T. harzianum has also become a promising system for xylanase production under appropriate conditions (Franco et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, T. harzianum has also become a promising system for xylanase production under appropriate conditions (Franco et al 2004). Castro et al (2010b) had previously shown that T. harzianum IOC3844 exhibited an expressive production of endoglucanase activity with a fast kinetics with the exponential production phase detected between 31 and 72 hours of fermentation after a short lag phase. In this work, under the same assay conditions, strain L04 showed a shorter lag phase with an earlier exponential production phase starting before 24 hours when grown on SCB.…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma reesei strains are probably some of the most reported, and this specie is frequently cited in reviews regarding cellulases production [64,65,97], being the source for the production of the majority of commercial cellulolytic preparations [98]. Further, microbial genera, such as Aspergillus, Gliocladium, Humicola, Penicillium, Sporotrichum, Streptomyces, Talaromyces, and Thermoascus, are commonly reported as outstanding producers of cellulolytic enzymes using agroindustrial materials as well [65,73,84,[99][100][101], so as other species from Trichoderma genus, such as Trichoderma harzianum [102,103].…”
Section: Cellulasesmentioning
confidence: 99%